Regarding the scope of competence of peacekeeping operations:: The comprehensive approach of UN military operation Sophia in view of the migration crisis (Journal of the Spanish Institute for Strategic Studies, 2018)
The evolution of the concept of Security in recent years has arisen from the appearance of complex crises that require the use of the full range of available means by both national and international actors. The migration crisis buffeting international relations in recent years is a clear example of this, and of the need to offer a comprehensive approach to those relations, having recourse to means from both national and foreign policies. In this area, the European Union naval operation Sophia is a clear paradigm as it is developing activities characteristic of a peacekeeping operation, along with others associated with internal security, such as the control of external maritime borders.
Keywords: Security; peacekeeping operation; maritime operation; Petersberg tasks; migrant crisis; comprehensive approach